PREFERENSI KONSUMEN BERAS DI PASAR KRIAN KABUPATEN SIDOARJO - Hidayat, Syarif Imam; Savitri, Silvy Emalia (Jurnal Social Economic of Agriculture, 2020)
Preference is subjective taste of individual for product or service. Preference becomes one of the determinant factors for consumption level of a product, includes rice. Rice consumption level is also impacted by difference in the level of consumer income. This study aims to analyze the preferences of rice consumers at Krian Market, Sidoarjo Regency.  This study was conducted at Krian Market, Sidoarjo Regency, using a method of non-probability sampling through accidental sampling by 50 respondents. The analysis tool was Importance Performance Analysis (IPA). The result showed that the highest score of importance level is flea pests-free, clean, and fluffier. It means that rice consumer preferences at Krian Market where rice that flea pests-free, clean, and fluffier.Keywords: Preferences and Rice Consumer.